The Supply Chain Analysis of Peanuts: A Case Study in Quang Nam Province of Vietnam - Thang Quyet Nguyen; Huynh Tan Nguyen (International Journal of Supply Chain Management, 2019)
This research was carried out to address the supply chain for peanuts production in Quang Nam province of Vietnam. To do so, the study randomly surveyed 170 peanut growers from three districts where have the largest cultivation areas of peanuts in Quang Nam province. Next, the research investigated some agencies that provided inputs and distributed outputs. All data obtained from the investigation was coded, and then imported into SPSS software for analysis. The research results demonstrated that supply chain of peanuts in Quang Nam province was relatively sophisticated, involving many stakeholders such as inputs suppliers, peanuts farmers, wholesalers, retailers and foreign importers. The outcome of this study also indicated that inputs for production were provided from three sources such as 22.3% from local agencies, 35.9% from tier 2 agencies and 41.8% from tier 1 agencies, meanwhile almost volume of peanuts was bought directly to wholesalers (about 82.8%) with payment either on credit or in cash. Furthermore, sale price varied in huge range, especially for domestic consumption channel, and foreign consumption of peanuts brought profit higher than domestic consumption. Importantly, the paper strongly recommended that the local authority should urge to enact policies to encourage cultivators to access official credit sources and to promote the export performance of peanuts. Lastly, this is the first research in Quang Nam relates to the analysis of the supply chain of peanuts. Hence, more studies should be undertaken to confirm these results for better policies.